Microbial community structure during fluoranthene degradation in the presence of plants - Storey, Sean; Mohd Ashaari, Mardiana; McCabe, Gráinne; Harty, Mary; Dempsey, Rita; Doyle, Owen; Clipson, Nicholas; Doyle, Evelyn (Wiley Online Library, 2014)
Aims: To investigate bacterial and fungal community structure during degradation of varying concentrations (0–5000 mg kg 1) of the polycyclic aromatic hydrocarbon (PAH) fluoranthene in the presence or absence of tomato plants. Method and Results: Fluoranthene amended or unamended growing media, with or without a plant, were incubated in pots in a glasshouse for 30 days. Fluoranthene concentration was quantified using GC-FID, while bacterial and fungal community structure was investigated using TRFLP and ARISA, respectively. The abundance of two ring hydroxylating dioxygenase genes was measured using qPCR. More fluoranthene was degraded in the presence of tomato plants at 500 and 5000 mg fluoranthene kg 1 (P < 0001), and it had a toxic effect on plant growth. Bacterial and fungal community composition in the rhizosphere was significantly different from that in nonrhizospheric and unplanted samples. The influence of fluoranthene on bacterial communities overcame that of the plant root such that community composition in rhizosphere and planted nonrhizospheric samples was broadly similar when fluoranthene was present. PAH-RHDa-GP genes were more abundant than PAH-RHDa-GN genes in all treatments. PAH-RHDa-GN abundance was unaffected by either PAH concentration or growing medium type, while the abundance of PAH-RHDa-GP was greatest in the rhizosphere. Conclusions: Plants promoted microbial growth and diversity and led to increases in abundance of Gram-positive dioxygenase genes, correlated with increased degradation of fluoranthene. Significance and Impact of the Study: This work contributes to knowledge in the broad area of biodegradation and also provides useful information for the design of future bioremediation strategies.